Posted by **Anonymous** on Tuesday, October 16, 2012 at 11:03pm.

Rewrite the expression as an algebraic expresion in x:

tan(sin−1x)=

- math -
**Anonymous**, Tuesday, October 16, 2012 at 11:04pm
sorry I meant tan(sin^-1 x)=

- math -
**Reiny**, Wednesday, October 17, 2012 at 8:41am
sin^-1 x is angle in a right - angled triangle where the opposite side is x and the hypotenuse is 1

let that angle be Ų

so really sin^-1 x ----> sinŲ = x/1

so the third side is √(1 - x^2)

then tan(sin^-1 x)

= tan Ų

**= x/√(1-x^2)**

check:

e.g. let x = .5

then sin^-1 (.5) = π/6

and tan(π/6) = .57735

according to my answer

tan(sin^-1 (.5)) = .5/√(1-.25) = .57735

all looks good.

## Answer This Question

## Related Questions

- Trigonometry - rewrite tan(sin^-14v) as an algebraic expression in v
- trig, precalc, math, algebra, trigonometry - Rewrite: tan(cos^−1 (v)) as ...
- math - simplify the following expression sin(v+x)-sin(v-x)? Rewrite the ...
- trigonometry - 1) Find the exact value of the expression: tan−1(tan(−...
- pre cal - Use identities to simplify each expression. sin(x)+cos^2(x)/sin(x...
- precalc - Find the exact value of each expression, if it exists: the -1 are ...
- Trig - Rewrite cos(tan^-1(v)) as an algebraic expression in v. Can someone help ...
- trig - Which expression is equivalent to tan(-x)cos^2x? -sin xcos x sin xcos x ...
- math-Trig - 1. Write the algebraic expression which shows Cos((ArcSin(4/X)), 2...
- Pre Calculus - Use one of the identities cos(t + 2šk) = cos t or sin(t + 2šk) = ...

More Related Questions